Ethylene controls translational gatekeeping to overcome flooding stress in plants. (17th August 2022) - Maric, Aida; Hartman, Sjon
Abstract : Protein synthesis is an essential but energetically expensive cellular process that is challenged under environmental stress in plants. Recent work demonstrates that the plant hormone ethylene, through GCN2, represses general translation during flooding stress to conserve energy. Moreover, ethylene also promotes the translation of specific stress‐responsive mRNAs to survive submergence stress. Abstract : Recent findings show that flooded plants conserve energy via rapid, ethylene‐induced translational stop that selectively ignores stress response transcripts.